DESAIN KURIKULUM PENDIDIKAN SENI TARI UNTUK PROGRAM PEMBINAAN BAGI WARGA BINAAN PEMASYARAKATAN PEREMPUAN - Sari, Alifatul Ratriana; Indar Sabri; Anik Juwariyah; Welly Suryandoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Dance arts coaching at Rutan Kelas II B Nganjuk has operated incidentally without adequate curricular foundations no competency standards, no structured material sequencing, and no standardized evaluation instruments. This condition undermines the rehabilitative function that should be central to the correctional system, particularly for female inmates who face multilayered psychological pressures. This study aims to design an adaptive, structured dance arts education curriculum that is responsive to the unique conditions of female inmates in correctional settings. A descriptive qualitative method was employed, with data collected through participatory observation, in-depth interviews with female inmates, correctional officers, and the Head of the Regional Office of the Directorate General of Corrections of East Java, alongside policy documentation review. Data analysis followed the interactive model of Miles. Three key findings emerged. First, the designed curriculum successfully shifts dependency away from the physical presence of instructors toward a self-directed, method-based instructional system, consistent with Clark's theory. Second, the modular design employing material segmentation techniques effectively accommodates variations in inmates' detention periods each individual can achieve complete competency regardless of sentence duration. Third, integrating a humanistic approach into the curriculum structure enables the simultaneous pursuit of Rineksapanala dance mastery and character rehabilitation alongside social reintegration goals. This curriculum is not merely an administrative document; it serves as a coaching instrument with direct implications for enhancing the quality of rehabilitation and social reintegration for female inmates.Dance arts coaching at Rutan Kelas II B Nganjuk has operated incidentally without adequate curricular foundations no competency standards, no structured material sequencing, and no standardized evaluation instruments. This condition undermines the rehabilitative function that should be central to the correctional system, particularly for female inmates who face multilayered psychological pressures. This study aims to design an adaptive, structured dance arts education curriculum that is responsive to the unique conditions of female inmates in correctional settings. A descriptive qualitative method was employed, with data collected through participatory observation, in-depth interviews with female inmates, correctional officers, and the Head of the Regional Office of the Directorate General of Corrections of East Java, alongside policy documentation review. Data analysis followed the interactive model of Miles. Three key findings emerged. First, the designed curriculum successfully shifts dependency away from the physical presence of instructors toward a self-directed, method-based instructional system, consistent with Clark's theory. Second, the modular design employing material segmentation techniques effectively accommodates variations in inmates' detention periods each individual can achieve complete competency regardless of sentence duration. Third, integrating a humanistic approach into the curriculum structure enables the simultaneous pursuit of Rineksapanala dance mastery and character rehabilitation alongside social reintegration goals. This curriculum is not merely an administrative document; it serves as a coaching instrument with direct implications for enhancing the quality of rehabilitation and social reintegration for female inmates.